Formalized Employee Search and Labor Demand - Lukas Hensel; Tsegay Tekleselassie; Marc Witte (Institute of Labor Economics (IZA), 2021)
Firms often use social networks to find workers, limiting the pool of potential applicants. We conduct a field experiment subsidizing firms' formal vacancy posting. The subsidies increase non-network employee search and shift vacancies towards high-skilled positions. Post-treatment, firms continue searching for high-skilled workers despite reverting to network-based search. This change in skill requirements does not increase vacancy posting or hiring, suggesting substitutability between workers of different skill levels. Finally, we experimentally show that information asymmetries about applicants' skills do not limit firms' formal search. Our results highlight that exposure to different labor market segments can permanently change firms' labor demand.
Keywords: D22; J23; J46; C93; 330; formalization; social networks; hiring; firms; field experiments